Humanitarianism torn between ethics and politics - Radovanović Bojana; Krstić Predrag (Temida)
This paper aims to provide an overview of the main landmarks and basic problems of humanitarianism, which is seen as a philosophy - an ethical response to suffering - but also as a practice in the form of humanitarian actions. There is general agreement that suffering ought to be alleviated, but not that humanitarian actions, and the humanitarian sector in general, are an adequate response. However, the practice of humanitarianism itself is not clearly demarcated. While for some it only refers to the actions aimed at eliminating or alleviating immediate suffering, others believe that humanitarianism requires dealing with the causes of suffering, and in its most extreme form, that humanitarianism requires force in the form of military intervention to stop suffering. Therefore, the objections to humanitarianism are contradictory - while on the one hand, its apolitical stances are respected in the name of timeless and decontextualized ethics, on the other its politicization is criticised. To condemn or praise humanitarianism, whether it comes from the point of ethics or politics, the authors conclude, it is important to always keep in mind what exactly is meant when referring to it.